2019
DOI: 10.7717/peerj.6577
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of long non-coding RNA expression profile in porcine circovirus 2-infected intestinal porcine epithelial cell line by RNA sequencing

Abstract: Porcine circovirus-associated disease (PCVAD), which is induced by porcine circovirus type 2 (PCV2), is responsible for severe economic losses. Recently, the role of noncoding RNAs, and in particular microRNAs, in PCV2 infection has received great attention. However, the role of long noncoding RNA (lncRNA) in PCV2 infection is unclear. Here, for the first time, we describe the expression profiles of lncRNAs in an intestinal porcine epithelial cell line (IPEC-J2) after PCV2 infection, and analyze the features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…HIV, porcine circovirus 2, HSV-1, rabies virus, avian leukosis virus J, bovine viral diarrhea virus) and parasites (e.g. Echinococcus granulosus, Cryptosporidium parvum, Cryptosporidium baileyi) in animals and humans [28,33,[66][67][68][69][70][71][72][73]. The expression profiles of host circRNAs were also elucidated after infections of avian leukosis virus J [74], bovine viral diarrhea virus [75], human cytomegalovirus [76], Orf virus [30], porcine endemic diarrhea virus [29], HIV [77], transmissible gastroenteritis virus [78], Mycobacterium tuberculosis [79], Clostridium perfringens [80] and C. baileyi [33].…”
Section: Discussionmentioning
confidence: 99%
“…HIV, porcine circovirus 2, HSV-1, rabies virus, avian leukosis virus J, bovine viral diarrhea virus) and parasites (e.g. Echinococcus granulosus, Cryptosporidium parvum, Cryptosporidium baileyi) in animals and humans [28,33,[66][67][68][69][70][71][72][73]. The expression profiles of host circRNAs were also elucidated after infections of avian leukosis virus J [74], bovine viral diarrhea virus [75], human cytomegalovirus [76], Orf virus [30], porcine endemic diarrhea virus [29], HIV [77], transmissible gastroenteritis virus [78], Mycobacterium tuberculosis [79], Clostridium perfringens [80] and C. baileyi [33].…”
Section: Discussionmentioning
confidence: 99%
“…Direct quantifications of the protein amounts after PCV2 infection revealed that there were altered levels of cytoskeletal proteins, stress response proteins, signal transduction proteins, and proteins involved in the ubiquitin-proteasome processes [ 32 , 51 ]. However, only one study had previously been performed to evaluate the effect of lncRNAs on PCV2 infection [ 25 ]. Fang et al used PCV2 to infect the porcine intestinal epithelial cell line IPEC-J2 to mimic porcine enteritis.…”
Section: Resultsmentioning
confidence: 99%
“…However, they used the p -value instead of the adjusted p -value to identify the altered lncRNAs and mRNAs, which would substantially increase the type I error, leading to false positive findings. For example, in their lncRNA list, no lncRNA identified has an adjusted p -value of less than 0.05 [ 25 ]. Therefore, in the current study, we aimed to study whether some differentially expressed lncRNAs could be found using more stringent screening parameters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations